Not Seen and Not Heard - Begel, Andrew; Hemphill, Libby (Microsoft Technical Report, 2011)
Virtual teams, in which the members work from multiple locations, have become a common feature at many global organizations. In spite of this new reality, collocated teams experience difficulties in adapting their established processes and practices for a newly virtual working environment, greatly impeding their performance, productivity, and morale. In this paper, we present findings from a qualitative case study of five software teams that hired and onboarded their first remote team member. Our analyses focus on three underappreciated aspects of the virtual onboarding process: trying to learn team practices as the team changes them, building and maintaining social relationships with physically remote teammates, and evaluating and managing expectations of performance from afar. From the results of our analyses, we pose seven propositions about virtual onboarding that should be explored in future studies.